Homeotherapy as a treatment of cauda equina syndrome in a cat: case report - Baldrich Romero, Nicolás Ernesto (2021)
At the Small Animal Clinic of the University of Amazonia, a female crossbreed feline arrives with a right pelvic limb neuromotor disorder, alteration of behavior and urinary and fecal incontinence. The tests performed showed kidney infection and Mycoplasma spp., A ventro-dorsal radiography of the lumbosacral region showed bilateral sacral-iliac dislocation, and consequent compression of the nerve roots of the vertebral canal, compatible with cauda equina syndrome. The implementation of a therapeutic protocol with 1% plus Neuralgo® and Inmul-V® (neural therapy), with applications of 0.1 ml in each intervertebral space and the femoral nerve of the affected limb, Cannabis sativa as an analgesic and physical therapies recovery of member functionality almost 100% in three weeks. This protocol reduced the recovery time and the presentation of side effects in the patient.